A Study of Idioms by Food in English and Vietnamese from a Perspective of Components / Khương Thị Thủy; NHDKH Đặng Nguyên Giang, Ph.D - Khương, Thị Thủy
The idioms by food are quite popular in both English and Vietnamese, and the components forming idioms can be analyzed from both structural and semantic perspectives. The researcher selected 162 idioms by food in English and 167 idioms by food in Vietnamese from the following dictionaries: Cowie, A. P., Mackin, R., & McCaig, I. R. (1993), Siefring, J. (2005), Nguyễn Lân (2003), Nguyễn Lực & Lương Văn Đang (2009),Tiêu Hà Minh (2007), Nguyễn Như Ý và các cộng sự (1998) with the purpose of investigated the idioms by food in English and Vietnamese from a perspective components. The study is aimed at three points: (1) uncovering how the components of idioms by food are organized structurally and semantically in English and Vietnamese, (2) finding out the similarities and differences between English and Vietnamese idioms by food in terms of structural and semantic components, (3) giving some implications for teaching and learning idioms by food through component analysis. This study was designed as a decriptive research with the method of componential analysis and contractive exploitation. According to the data analysis, the result of the study show that the structural components of idioms by food belong to three types: symmetrical idioms by food, similized idioms by food, and non-symmetrical idioms by food. The semantic components of idioms by food are divided into trasparent, semi-transparents, semi-opaque and opaque.It means that most of idioms by food in English and Vietnamese are possibly interpretable.